Brimonidine–montmorillonite hybrid formulation for topical drug delivery to the eye. Issue 35 (29th July 2020) - Park, Chun Gwon; Choi, Goeun; Kim, Myung Hun; Kim, Se-Na; Lee, Hanna; Lee, Na Kyeong; Choy, Young Bin; Choy, Jin-Ho
Abstract : Ternary hybrids of brimonidine, montmorillonite and polyvinyl alcohol (BMD-MMT@PVA) can improve ocular drug bioavailability when administered topically to the eye. Abstract : Brimonidine (BMD) is often prescribed as an eye drop to reduce the intraocular pressure (IOP) for glaucoma treatment. However, eye drops are limited by rapid clearance from the preocular surface, and hence a low ocular drug bioavailability. Therefore, in this study, we propose montmorillonite (MMT), as a delivery carrier, hybridized with BMD (BMD–MMT) for topical drug delivery to the eye. The BMD–MMT hybrid was prepared by intercalating the BMD molecules in the interlayer space of the MMT lattice via ion-exchange reaction; it was then formulated with polyvinyl alcohol (PVA) to produce a dry tablet ( i.e., BMD–MMT@PVA). The BMD–MMT@PVA hybrid drug released BMD in a sustained manner for more than 5 h under in vitro conditions. When the hybrid drug was administered to rabbit eyes in vivo, 43% and 18.5% BMD–MMT still remained on the preocular surface for 10 and 60 min after administration, respectively. Thus, the BMD–MMT@PVA hybrid drug exhibited a prolonged decrease in IOP, that is, for 12 h, which was approximately two times longer than that observed with the commercially available BMD eye drop, Alphagan® P.